Application of three-dimensional numerical study in air-blast atomizer designing - Sipatov, Aleksey Matveevich; Karabasov, Sergey Aleksandrovich; Gomzikov, Leonid Yulievich; Abramchuk, Taras Viktorovich; Semakov, Gleb Nikolaevich (Computational Continuum Mechanics, 2013)
The experience gained from modifying the low-pressure drop gas-turbine fuel atomizer with two air nozzles is presented. The volume of fluid (VOF) approach was used for two-phase flow analysis. Comparison of the base design and the design, obtained from numerical analysis results, was executed by a full-scale experiment. Experimental data for particle velocities and particle diameter data were obtained at the ICMM UB RAS (Perm, Russia). It is shown that the VOF approach provides sufficient conditions for identification of such effects as significant irregularity of the spray in the circumferential direction. Elimination or reduction of the causes of this event can significantly improve the spray quality without significant changes in the design.